Field evaluation and break-even analysis of specialty soybeans for biodiesel and meal protein production. Issue 1 (2nd January 2018) - Stobaugh, Bryan; Chen, Pengyin; Jaureguy, Luciano M; Florez-Palacios, Liliana; Orazaly, Moldir; Zeng, Ailan
ABSTRACT: The economic value of a soybean [Glycine max (L.) Merr.] crop depends on yield and quality. The objectives of this study were to evaluate soybean lines for protein and oil content and to examine the break-even (BE) analysis of these traits combined with yield. Forty lines of maturity group (MG) IV or V were grown at four Arkansas locations for two years. Yield, protein, and oil content of each line were determined and compared to the check average for a BE comparison of the total economic value of the line. Results showed six profitable lines ($8.40 to $54.96 per metric ton based on yield) in 2008 and six profitable lines ($0.49 to $61.19 per metric ton based on yield) in 2009. Overall, in both MG, high-protein lines needed to yield more to be profitable, whereas high-oil lines had competitive yield, protein and oil content; R00-764 (MG IV), R05-71 (MG V), and R02-6185F (MG V) were competitive without added premiums.